THE INFLUENCE OF PHYSICAL ENVIRONMENT, NON-PHYSICAL ENVIRONMENT, WORK CULTURE, TRANSFORMATIONAL LEADERSHIP STYLE ON EMPLOYEE JOB SATISFACTION - Saputra, Seno; Fatimah, Feti; Rahayu, Jekti (Dynamic Management Journal, 2024)
This study's main goal is to find out how different aspects of the workplace culture, both tangible and intangible, and transformational leadership affect workers' job satisfaction. This study uses a quantitative methodology to investigate the connections and influences between these variables. The study specifically aims to evaluate how work culture, non-physical environmental factors, physical environmental circumstances, and transformational leadership style affect employees' job satisfaction at CV Dira Kencong Shopping Center and Waterpark in Jember. The research aims to ascertain whether the mentioned characteristics exist and how much of an impact they have on the job satisfaction variable for CV employees at Dira Kencong Shopping Center and Waterpark in Jember. It does this by using quantitative descriptive methodology. The result 3 variable transformational leadership style taken together.